Repurposed Antimicrobial Combination Therapy: Tobramycin-Ciprofloxacin Hybrid Augments Activity of the Anticancer Drug Mitomycin C Against Multidrug-Resistant Gram-Negative Bacteria - Domalaon, Ronald; Ammeter, Derek; Brizuela, Marc; Gorityala, Bala Kishan; Zhanel, George G.; Schweizer, Frank (Frontiers in Microbiology, 2019)
The lack of therapeutic options to treat infections caused by multidrug-resistant (MDR) pathogens, especially Gram-negative bacteria, is apparent. Therefore, it is imperative to develop new strategies to address the problem of antimicrobial resistance. Repurposing non-antibiotic commercial drugs for antimicrobial therapy presents a viable option. We screened six anticancer drugs for their potential use in antimicrobial therapy. Here, we provide in vitro evidence that suggests feasibility to repurpose the anticancer drug mitomycin C against MDR Gram-negative bacteria. We also demonstrated that mitomycin C, etoposide and doxorubicin were affected by drug efflux in Pseudomonas aeruginosa. In combination with a tobramycin-ciprofloxacin antibiotic hybrid (TOB-CIP), the antibacterial activity of mitomycin C was enhanced against MDR clinical isolates of P. aeruginosa, Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae. In fact, 4 μg/mL (3 μM) TOB-CIP reduced the minimum inhibitory concentration of mitomycin C to ≤1 μg/mL against MDR Gram-negative bacteria, except A. baumannii. We showed that synergy was inherent to TOB-CIP and that neither tobramycin nor ciprofloxacin individually synergized with mitomycin C. Our finding supports identifying adjuvant partners for mitomycin C, such as TOB-CIP, to enhance suitability for antimicrobial therapy.